2018
DOI: 10.1108/ijppm-03-2016-0060
|View full text |Cite
|
Sign up to set email alerts
|

Improving job performance through identification and psychological capital

Abstract: Purpose The purpose of this paper is to increase understanding of the link between various identification foci and performance, and to test whether one’s psychological capital (PsyCap) can explain the influence of collective or relational identification on job performance. Design/methodology/approach The study sample comprised 235 academicians working in a foundation university from Turkey. The questionnaires were practiced in two different time intervals with using an identifier coding system for avoiding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 77 publications
(118 reference statements)
1
23
0
2
Order By: Relevance
“…In addition, another study by Testa, Corsini, Gusmerotti and Iraldo (2018) showed that personal attitudes and PsyCap through selfefficacy influence OCB. This is also supported with other studies (Machmud, 2018;Shefer, Carmeli, & Cohen-Meitar, 2018;Tüzün, Çetin, & Basim, 2018) using samples of employees from different professions in Europe. Akin (2017) in his research using multiple regression analysis established that PsyCap through optimism predicts OCB.…”
Section: Empirical Literature Review the Relationship Between Psychological Capital And Organisational Citizenship Behavioursupporting
confidence: 90%
“…In addition, another study by Testa, Corsini, Gusmerotti and Iraldo (2018) showed that personal attitudes and PsyCap through selfefficacy influence OCB. This is also supported with other studies (Machmud, 2018;Shefer, Carmeli, & Cohen-Meitar, 2018;Tüzün, Çetin, & Basim, 2018) using samples of employees from different professions in Europe. Akin (2017) in his research using multiple regression analysis established that PsyCap through optimism predicts OCB.…”
Section: Empirical Literature Review the Relationship Between Psychological Capital And Organisational Citizenship Behavioursupporting
confidence: 90%
“…A meta-analysis including studies with over 12,000 employees found PsyCap to be predictive of self-rated, supervisor-rated, objective performance, and desirable employee attitudes such as job satisfaction, commitment, and psychological well-being [9]. These findings correspond with findings among 235 other participants determining positive effects of PsyCap on employee job performance [10].…”
Section: Introductionmentioning
confidence: 52%
“…A considerable amount of recent studies have drawn similar conclusions regarding PsyCap's effectiveness as a personal resource in predicting work-related outcomes and individual behaviour (e.g. Pitichat et al , 2018; Tüzün et al , 2018; Aybas and Acar, 2017; Milosevic et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 77%